1992
DOI: 10.1021/la00047a007
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of localized adsorption of colloid particles

Abstract: Kinetics of localized adsorption of charged colloid particles on homogeneous solidlliquid interfaces was analyzed. Limiting analytical equations were formulated for the maximum surface concentration e ,, the blocking parameterB(O), and adsorption kinetics in terms of the lateral interaction parameter h* depending on the ionic strength of the colloid suspension. In the general case particle adsorption kinetics proceeding according to the random sequential adsorption (RSA) mechanism was simulated numerically by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
68
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 0 publications
3
68
1
Order By: Relevance
“…Thus, a particle arriving at the surface is accepted if it does not overlap with a previously adsorbed one; otherwise it is rejected. Specific quantities, such as the maximum coverage of the surface, or jamming limit, are in accordance with some experimental results [3] [4] [5], so it was concluded that RSA was a good model when particles diffuse to the surface. However, further numerical studies which took into account the diffusion showed discrepancies in the pair distribution function [6].…”
supporting
confidence: 77%
“…Thus, a particle arriving at the surface is accepted if it does not overlap with a previously adsorbed one; otherwise it is rejected. Specific quantities, such as the maximum coverage of the surface, or jamming limit, are in accordance with some experimental results [3] [4] [5], so it was concluded that RSA was a good model when particles diffuse to the surface. However, further numerical studies which took into account the diffusion showed discrepancies in the pair distribution function [6].…”
supporting
confidence: 77%
“…The adsorption of latex spheres onto a flat solid surface is a simple experimental model system, on which considerable work has been done. An optical microscope permits the direct observation of structural properties of the adsorbed layer [11,12]. This apparently simple phenomenon involves several fundamental processes that govern the kinetic behavior of the system and the structure of the adsorbed layer.…”
mentioning
confidence: 99%
“…The adsorption of latex spheres onto a flat solid surface is a simple experimental model system, on which considerable work has been done. An optical microscope permits the direct observation of structural properties of the adsorbed layer [11,12].…”
mentioning
confidence: 99%
“…Its validity for describing adsorption processes is less clear. Although it seems to predict quite accurately the radial distribution function, g(r), of the assembly of the adsorbed particles (6,7), it leads to contradictory results as far as the density fluctuations of adsorbed particles is concerned. This latter is measured by the reduced variance (ratio of variance 2 to mean ͗n͘) of the distribution of the number of particles deposited on a great number of subsurfaces of equal size that are part of the deposition plane (6,8).…”
mentioning
confidence: 99%